Bibliometric analysis of prominent topics in global scientific production on sustainable development goals in Scopus (2013–2022) - Mario E. Diaz-Barrera; Crayla Alfaro-Aucca; Josmel Pacheco-Mendoza; Moisés Moreno-Albarrán; Edgard Fernando Pacheco-Luza; Carlos Enrique Rengifo Chunga (Discover Sustainability)
Abstract The Sustainable Development Goals (SDGs) are an action plan proposed by the United Nations to improve the quality of life of all people in the world by 2030. This paper explores the levels of accomplishments proposed by the UN in terms of the resulting scientific production. Measuring the scientific production linked to each of the objectives in each period allows estimating the scholarly efforts made to respond to the challenges proposed by each objective in the short term. The SciVal platform was used to consult and analyze the scientific production for each goal published in Scopus (2013–2022). The indicators generated by the platform were used to characterize the scientific production, its impact, collaboration percentages and the prominent themes in each field. Scientific production related to SDGs accounted for 28% of global production. Those with greater scientific production have been health (ODS3) and energy (ODS7). The COVID-19 pandemic may have had an impact on the overall scientific production. The main themes within each goal show high impact indicators, but with moderate indicators of international collaboration, suggesting that international efforts aimed at SDGs may only be from a few countries. Among the most important cross-cut concepts of the main themes to all objectives are climate change, air quality, domestic violence, ecosystem, gestation, and democracy. The results of this study highlight the thematic impact of each concept on sustainable development in general beyond a single objective. The United States and China are the countries with the highest scientific production for sustainable development.